Tlingit housepost of tired wolf (originally from Tongass), Saxman, Alaska, July 1939 - Schallerer, Otto
House post of wolf seen from the side, with tongue hanging out. In background can be seen a white bear post, and a house. Note from unidentified source: One of a pair of houseposts from Tongass called the Tired Wolf; this post has a face carved in wolf's eye. Repaired and set up at Saxman National Monument [Saxman Totem Park] In Garfield Collection, 130/4/5